Handbook of personality dynamics and processes - Rauthmann, John F., 1987- (Academic Press, 2021)
The Handbook of Personality Dynamics and Processes is a primer to the basic and most important concepts, theories, methods, empirical findings, and applications of personality dynamics and processes. This book details how personality psychology has evolved from descriptive research to a more explanatory and dynamic science of personality, thus bridging structure- and process-based approaches, and it also reflects personality psychology's interest in the dynamic organization and interplay of thoughts, feelings, desires, and actions within persons who are always embedded into social, cultural and historic contexts. The Handbook of Personality Dynamics and Processes tackles each topic with a range of methods geared towards assessing and analyzing their dynamic nature, such as ecological momentary sampling of personality manifestations in real-life; dynamic modeling of time-series or longitudinal personality data; network modeling and simulation; and systems-theoretical models of dynamic processes.